Effects of Freshwater Protected Areas on Survival of a Critically Endangered Cetacean - Yi Han; Wenjing Xu; Kexiong Wang; Ding Wang; Zhigang Mei (Conservation Letters)
ABSTRACT Evaluating the effectiveness of freshwater protected areas (FPAs) is crucial for improving their performance, yet evidence remains limited. Using remote sensing and field surveys from 2001 to 2017, we examined FPA coverage, their efficacy in preventing species decline and habitat deterioration, and strategies to enhance FPA effectiveness for the critically endangered Yangtze finless porpoise (Neophocaena asiaeorientalis asiaeorientalis). FPAs failed to cover nearly half of high‐abundance regions and two thirds of medium‐abundance areas. Despite initially better conditions, FPAs experienced similar or greater species declines and habitat deterioration. Porpoise distribution closely correlated to habitat conditions, with abundance declining most in severely degraded floodplains while remaining stable or increasing in less disturbed areas. To improve FPA performance, we recommend expanding protection to medium‐ and high‐abundance areas to better cover key porpoise habitats and enhancing existing FPAs through stricter law enforcement, proactive management, and targeted restoration. These strategies are reinforced by China's new legal and policy framework for Yangtze River protection, providing a foundation for long‐term conservation.